Representasi Perjuangan Ras Kulit Hitam Pada Series The Falcon And Winter Soldier - Catur Sunu Wijayanto; Fitria Iswari (Gandiwa Jurnal Komunikasi, 2023)
Series-based films are another form of film that is deliberately made in a series of several short films that break the plot as a whole into several episodes. As it is known today as "The Avengers". Captain America, which was originally held by Steve Rogers, is now taken over by Sam Wilson or commonly called Falcon. The story of Sam Wilson who eventually transformed into Captain America is told in the form of a series titled The Falcon and Winter Soldier. The method used in this study is the theory of visual culture according to Nicholas Mirzoeff in a book by Margaret Dikovitskaya, 2005. This paper aims to show that the issue of racism is still a social issue that is intensively fought, because differences should not be a problem for every human being to continue to support each other. Anyone deserves respect no matter what their background, and appearance. In this series, which has a superhero theme with six episodes, it depicts how a person struggles to believe in himself and fight for his right as a human being to gain the trust of American society.Â  However, the journey was not easy, Sam Wilson as the main pawn of this film had to struggle with many problems until in the end he ventured to become Captain America. At the same time, fighting for his people, that is, black people to get the honor that should be as human beingsÂ Â